A retrospective analysis on the product recall due to solvent and mineral residue issues. (March 2023) - Ahmed, Salman; Musyuni, Pankaj; Aggarwal, Geeta
Drug recalls are essential to maintaining the safety process because the medical industry's top objective is primarily to deliver higher-quality goods to a larger population. They do this by eliminating subpar products from the market. Drug recalls are increasing quickly as a result of increased investigation rates, the emergence of industrialization and the online era into the sector, and regulatory authorities and health experts are now focusing on more stringent regulations to prevent further recalls of faulty pharmaceutical drugs. The purpose of the present write-up is to give an overview of how drug recalls work with the help pf examples of recalls due to presence of undesired solvents and mineral residue, how they affect the pharmaceutical business, and what can be done to stop them.